The mediating role of primary TQM factors and strategy in the relationship between supportive TQM factors and organisational results: An empirical assessment using the MBNQA model - Mohammed H. Alanaz (Cogent Business & Management, 2020)
The mediating role among total quality management and business excellence model factors, including the role of strategy, has rarely been addressed empirically. This research examines the mediating effects of primary total quality management factors (operations management and measurement, analysis, and knowledge management) and strategy on the relationship between supportive total quality management factors (leadership, workforce, and customers) and organisational results using the Malcolm Baldrige National Quality Award (MBNQA) model as the framework. Based on responses from managers of 217 Saudi firms, the questions and hypotheses suggested in this research are examined using the structural equation modelling technique. The results show that: (a) supportive factors enhance primary factors; (b) strategy mediates the relationship between supportive factors and primary factors; (c) primary factors mediate the relationship between supportive factors and results; and, more importantly, (d) collectively and sequentially, the combination of strategy and primary factors mediates the relationship between supportive factors and results more strongly than their respective individual mediation effects separately. The findings support the systems perspective provided by the MBNQA model.
Keywords: 650; TQM; MBNQA; mediation effects; supportive TQM factors; primary TQM factors; structural equation modelling